A STUDY OF CUSTOMER SATISFACTION WITH VEGETABLE SAUCES - Svetlana Yur’evna Glebova; l’ga Valentinovna Golub; Nataliya Ivanovna Davydenko; Velentina Ivanovna Bakaitis (Современная наука и инновации)
In article on the basis of the results of our research the results of findings to identify important consumer characteristics of vegetable sauces; the definition of the relationship between it and customer satisfaction using the Kano model are shown.